Traditional manufacturing of hard cheese - kachkaval on Stara Planina mountain - Mijačević, Zora (Acta agriculturae Slovenica, 2004)
Nomads from Greece implemented the tradition of kachkaval cheese making on Stara Planina, 100 years ago. At the beginning, the kachkaval was made exclusively from sheep's milk, during the graying period. In the past, kachkaval was made on "bačija" dairies, and besides the kachkaval the significant by-products were ghee and "urda". The historical data showed that in the year 1903, 160 wagons of kachkaval were exported to Vienna and Budapest. The changes in animal breeding conditions and increasing number of cattle in this region lead to significant reduction in number of sheep, and consequently caused the discontinuance in production of kachkaval. Nowadays, there are few "bačija"-dairies on Stara Planina Mountain which are producing kachkaval in the traditional way. The characteristics of chemical content of traditionally produced kachkaval are: 60.79 3.37% dry matter, 29.50 2.25% milk fat, 55.57 3.55% moisture on a fat-free basis, 48.52 2.41% fat in dry matter, 24.99 1.60% proteins, 3.8 2.57% NaCl and pH value 5.62 0.09. The traditionally made kachaval has a shape of a flatten cylinder, with the weigh of 6-7 kg, bright-yellow crust and firm dough. The traditional cheese making of kachkaval comprises the hand made process of "pasta filatta" cheese and forthe end product a spicy and salty taste are typical. Revitaliying the traditional kachkaval production also means the preservation of cultural identity of the region of Stara Planina.
Keywords: mlečni izdelki; sir; kačkavalj; izdelava